A parent-implemented embedded AAC intervention for teaching navigational requests and other communicative functions to children with Autism spectrum disorder. - Gevarter, Cindy; Groll, Mariah; Stone, Erin; Najar, Adriana Medina (Augmentative and alternative communication (Baltimore, Md. : 1985), 2021)
This study evaluated the effectiveness of an embedded naturalistic intervention for teaching augmentative and alternative communication (AAC) application responses to three preschool-aged males with autism spectrum disorder (ASD). Parents were taught to embed opportunities for their child to communicate with a grid-based AAC application during every-day routines such as play or mealtime. Communication targets included requesting objects using two-step taxonomic navigational responses, and requesting assistance, rejecting items, or making social comments/responses using a two-step message-strip response. During intervention, parents used strategies such as time delay, prompting, reinforcement, and device proximity (faded over time) to encourage target responses. Display formats and intervention targets were selected in consideration of prior dynamic assessment results. Effects of intervention were evaluated using a multiple probe across participants design. For functional navigational AAC item requesting, all three participants showed an immediate increase in responding that maintained at high levels. Functional AAC responding for other communicative purposes also increased, but at a more gradual pace. All three participants showed generalized responding when new items were added to displays, and when display pages with a larger array of folders and vocabulary items were introduced. Generalization to labeling tasks was mixed. © 2021 International Society for Augmentative and Alternative Communication.
4 citations (Crossref) [2023-10-31]
Keywords: Alternative communication; Augmentative and alternative communication application; Augmentative-and-alternative communication; Autism spectrum disorders; Communication application; Communicative functions; Diseases; Embedded instruction; Human rehabilitation engineering; Naturalistic intervention; Navigation; Steps responding; Two-step responding; dept.cmd; peer-reviewed

Naturalistic communication training for early intervention providers and latinx parents of children with signs of autism. - Gevarter, Cindy; Najar, Adriana Medina; Flake, Jennifer; Tapia-Alvidrez, Felicia; Lucero, Alixandria (Journal of developmental and physical disabilities, 2021)
In this study, researchers implemented a brief training plus coaching program in naturalistic developmental behavioral intervention with three participant triads. Each triad consisted of an early intervention provider, an English-speaking Latinx parent, and that parent’s young child with autism spectrum disorder (ASD) or early signs of ASD who had limited vocal speech. The effects a single training session, plus two researcher coaching sessions were evaluated using a nonconcurrent multiple probes across participants design. Primary dependent variables included (a) the number of completed targeted communication turns between the parent and child and (b) the number of child independent target communication responses (gestures and manual signs) during family-selected routines. Additional measures examined whether parents used strategies taught to them during training, and whether early intervention providers addressed strategies taught via coaching. A social validity measure was used to determine parent and provider views of the training. Due to COVID-19 restrictions, training and post-training sessions were delivered via telehealth for two triads. While data trends and variability differed across triads, following training, all three families increased the number of completed target communication turns and all three children showed higher rates of independent communication responses. Parents and providers implemented strategies taught and reported positive effects of the program. Implications regarding the use of naturalistic intervention methods for Latinx families, the utility of brief training models to meet the needs of under-resourced early intervention programs, and potential uses of telehealth are discussed. © 2021, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.
9 citations (Crossref) [2023-10-31] https://www.ncbi.nlm.nih.gov/pmc/articles/PMC8079838 ; https://europepmc.org/article/MED/33935477 ; https://link.springer.com/content/pdf/10.1007/s10882-021-09794-w.pdf ; https://www.scilit.net/article/c889ef228cfa367aafde22446e957a7d?action=show-references ; https://pubmed.ncbi.nlm.nih.gov/33935477/
Keywords: dept.cmd; peer-reviewed

Correction to: Abnormalities of aspiration and swallowing function in survivors of acute respiratory failure - Langmore, Susan E.; Krisciunas, Gintas P.; Warner, Heather L.; White, S. David; Dvorkin, Daniel; Fink, Daniel S.; McNally, Edel; Scheel, Rebecca; Higgins, Carrie; Levitt, Joseph E.; McKeehan, Jeffrey; Deane, Sandra; et al. (Dysphagia, 2021)
Due to the errors occurred in the originally published version, this article is being reprinted in its entirety as Correction. All errors have been corrected. It is the correct version. © 2021, Springer Science+Business Media, LLC, part of Springer Nature.
1 citations (Crossref) [2023-10-31]
Keywords: dept.cmd; erratum; peer-reviewed

Empirical insights into college students’ academic reading comprehension in the united states - Kalbfleisch, Elizabeth; Schmitt, Elena; Zipoli, Richard P. (Journal of College Reading and Learning, 2021)
This article reports on a collaborative research project involving faculty in writing studies, communication disorders, and applied linguistics that sought to empirically describe the reading skills of students (N = 910) in freshman composition classes at one college and two universities in the northeast United States. The research team developed and administered a questionnaire that evaluated students’ reading abilities according to six categories: inferential ability, background knowledge, general comprehension, vocabulary, figurative language/jargon, and morphosyntactic structures (grammar/syntax). Our statistically significant results showed that students scored best in the categories of background knowledge and general comprehension, which are well researched in a college population. However, students struggled in categories such as figurative language/jargon and morpho-syntactic structures, which are not well researched in a college population. Further, comprehension seemed generally discrete (understanding specific points of an essay) rather than holistic (indicated by an ability synthesize those points into a general statement about the author’s thesis). These findings suggest that further empirical research in this area will help describe the reading skills of college students and consequently will inform the development of pedagogical approaches that more effectively address students’ current needs. © 2021 College Reading and Learning Association.
2 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85101017685
Keywords: dept.cmd; dept.eng; dept.wll; peer-reviewed